IDENTIFICAÇÃO DE ANIMAIS SILVESTRES DE INTERESSE CRIMINAL DA FAUNA MATOGROSSENSE POR MEIO DE DNA MITOCONDRIAL - Carmo, Reginaldo Rossi do (2012)
Brazil has an undeniable importance in the scenario of global biodiversity, what turns it one of the most sought countries for this is the third largest illicit trade of the world, the traffic of wild animals. To cope with the criminal assaults Brazil has been improving its environmental legislation and the expert work has gained special importance in quantifying the damage and identifying the species involved in criminal activities. Most of the experts are used of comparative morphological identification of the work, howevwe, it is common for the seizure of only fragments of specimens and, most often in these cases the identification is only possible by the technique of gene sequencing. Even with the recognition of technology as an important tool for identification, it still hangs a discussion about the best DNA segment to be used (Cytb or COI) and if these are effective for degraded samples, as forensic samples. Aiming to contribute to dissolution of these questions and to deposit in the international database GenBank, the mitochondrial DNA sequences generated. The samples were divided in two groups, calls of reference samples (collected from animals in the UFMT`s zoo) and questioned samples (sent to the POLITEC laboratory for specific identification). After extraction, amplification and sequencing, the resulting sequences were compared with sequences already deposited in GenBank. For the parameters used in this study, the best results were obtained for the shortest Cytb sequences. In only 10% of species could be successful in sequencing of the COI segment. The resulting sequences of sample references, when confronted with sequences deposited in database presented similarity among 93.9% to 100% except for the Leopardus pardalis sample that resulted in 91.9% of similarity with the species Prionailurus bengalensis. For the resulting sequences of the questioned samples we obtained similarity index above 97% for species of Hydrochoerus hydrochaeris, Tapirus terrestris (initially taken as Dasyprocta agouti) and Euprhactus sexcinctus. The direct confrontation between the reference and the questioned sample of the species Leopardus pardalis presented index of superior similarity of 99%. For the obtained sequences of the species Pecari tajacu, Rhynchotus rufescens, Leptotila sp. and Tupinambis sp., the similarity index was of 94.3% with Pecari tajacu, 96.5% with Ramphastos toco, 96.1% with Amazon guildingii and 98.3% for the species Tupinambis merianae, respectively. Thus, this study contributes to show the efficiency of the technique and also exposes the need to undertake a great project to sequence the whole Brazilian wild fauna to make available them in the public databases.